1996
DOI: 10.1088/1538-4357/462/1/l17
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Confirmation of a Population of Normal Star-forming Galaxies at Redshifts z > 3

Abstract: We report the discovery of a substantial population of star-forming galaxies at 3.0 < ∼ z < ∼ 3.5. These galaxies have been selected using color criteria sensitive to the presence of a Lyman continuum break superposed on an otherwise very blue far-UV continuum, and then confirmed with deep spectroscopy on the W. M. Keck telescope. The surface density of galaxies brighter than R = 25 with 3.0 < ∼ z < ∼ 3.5 is 0.4 ± 0.07 galaxies arcmin −2 , approximately 1.3% of the deep counts at these magnitudes; this value a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
429
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(453 citation statements)
references
References 29 publications
23
429
1
Order By: Relevance
“…These are ultraviolet (UV)-selected star-forming galaxies first characterised by Steidel et al (1996) at z ß3. At these redshifts, the galaxies are observed to have low flux (i.e.…”
Section: Early Work With Long-slit Spectroscopymentioning
confidence: 99%
“…These are ultraviolet (UV)-selected star-forming galaxies first characterised by Steidel et al (1996) at z ß3. At these redshifts, the galaxies are observed to have low flux (i.e.…”
Section: Early Work With Long-slit Spectroscopymentioning
confidence: 99%
“…where light is generated by stars) at high redshifts has seen a tremendous progress in the last years thanks to programs employing the Lyman break technique (cf. Steidel et al 1995Steidel et al , 1996Steidel et al , 1999, and projects like the Hubble Deep Field (HDF, Williams et al 1996). Steidel and collaborators (1996) have shown that on the order of a few percent of the galaxies at faint optical magnitudes (R ∼ 25) are actively star forming galaxies at redshift greater than 3.…”
Section: Star Forming Galaxies At High Redshiftmentioning
confidence: 99%
“…9 At z > 1.7, where the [O ii] emission line at 3,727Å is no longer detectable in the optical window, we are beginning to find objects on the basis of their UV absorption lines. [10][11][12][13] These objects may be starbursting galaxies, in some cases with active galaxy (AGN) activity.…”
mentioning
confidence: 99%